Simultaneous Determination of Paracetamol, Chlorzoxazone and Diclofenac Sodium in Tablet Dosage Form by High Performance Liquid Chromatography - Madhukar A. Badgujar; Satish G. Pingale; Kiran V. Mangaonkar (E-Journal of Chemistry)
A simple, precise and rapid isocratic reverse phase high performance liquid chromatographic method was developed for the simultaneous determination of paracetamol, chlorzoxazone and diclofenac sodium from tablet dosage form. The chromatographic separation was performed on an inertsil C18 column (250 mm × 4.6 mm i.d 5 µm particle size). Mobile phase consisted of a mixture of phosphate buffer (0.02 M KH2PO4, pH adjusted to 3.7 using orthophosphoric acid), acetonitrile and methanol in the ratio of (25: 25: 50) at a flow rate of 1.0 mL/min. The wavelength was set at 220 nm. The proposed method was validated for linearity, accuracy, precision, LOD and LOQ. The calibration was linear over the range of 50-150 µg/mL for paracetamol, 50-150 µg/mL for chlorzoxazone and 5-15 µg/mL for diclofenac sodium. The retention times were found as 2.8 min for paracetamol, 4.2 min for chlorzoxazone and 6.4 min for diclofenac sodium. The method can be easily adopted for quality control analysis.